2001
DOI: 10.1038/sj.gt.3301542
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive, quantitative imaging in living animals of a mutant dopamine D2 receptor reporter gene in which ligand binding is uncoupled from signal transduction

Abstract: The dopamine D2 receptor (D2R) has been used in adenoviral delivery systems and in tumor cell xenografts as an in vivo reporter gene. D2R reporter gene expression has been non-invasively, repetitively and quantitatively imaged by positron emission tomography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(95 citation statements)
references
References 27 publications
1
93
0
1
Order By: Relevance
“…[42][43][44] Therefore, the use of hSSTr2 should be advantageous as a reporter receptor in cancer, although there may be concern for its effects in normal tissues. In this regard, it may be advantageous to uncouple ligand binding from signal transduction as suggested by Liang et al and as they have demonstrated with D 2 R. 23 The former is another concern for using hSSTr2 as a reporter receptor, thus, HAhSSTr2 could address this. Insertion of the HA sequence into the N-terminus of the receptor did not appear to have deleterious effects with regard to ligand binding as shown in Figures 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44] Therefore, the use of hSSTr2 should be advantageous as a reporter receptor in cancer, although there may be concern for its effects in normal tissues. In this regard, it may be advantageous to uncouple ligand binding from signal transduction as suggested by Liang et al and as they have demonstrated with D 2 R. 23 The former is another concern for using hSSTr2 as a reporter receptor, thus, HAhSSTr2 could address this. Insertion of the HA sequence into the N-terminus of the receptor did not appear to have deleterious effects with regard to ligand binding as shown in Figures 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…The type 2 dopamine receptor (D 2 R) and the human somatostatin receptor subtype 2 (hSSTr2) have also been used as reporter genes. 3-(2 0 -18 F-fluoroethylspiperone and 11 Craclopride have been used to image D 2 R by PET, 18,22,23 while 99m Tc-P829, 188 Re-P829, 99m Tc-P2045, and 111 In-DTPA-D-Phe 1 -octreotide have been used to image hSSTr2 with a gamma camera. [24][25][26] Also, it has been demonstrated that two genes can be expressed simultaneously either through the use of an internal ribosomal entry site or by placing each gene in series under the control of separate promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the somatostatin receptor gene 5,6 the HSV1-tk gene [9][10][11][12][13][14][15] and the D2R gene 8,20 have been the subject of the most extensive analyses for in vivo reporter gene development, using positron-emitting, radiolabeled probe detection systems.…”
Section: Discussionmentioning
confidence: 99%
“…FHBG injection and microPET analysis was repeated six times for each mouse in an 88 day period. 14 and a control replication-deficient adenovirus (ad.v) 20 were also used in experiments reported here.…”
Section: Construction and Purification Of Recombinant Adenovirusmentioning
confidence: 99%
See 1 more Smart Citation